A Comprehensive Tyrosine Phosphoproteomic Analysis Reveals Novel Components of the Platelet CLEC-2 Signaling Cascade - Izquierdo, Irene; Barrachina, María N.; Hermida-Nogueira, Lidia; Casas, Vanessa; Morán, Luis A.; Lacerenza, Serena; Pinto-Llorente, Roberto; Eble, Johannes A.; de los Ríos, Vivian; Domínguez, Eduardo; Loza, María I.; Casal, José Ignacio; Carrascal, Montserrat; Abián, Joaquín; García, Angel (Thrombosis and Haemostasis, 2020)
C-type lectin-like receptor 2 (CLEC-2) plays a crucial role in different platelet-related physiological and pathological processes. It signals through a tyrosine kinase-mediated pathway that is highly dependent on the positive feedback exerted by the platelet-derived secondary mediators, adenosine diphosphate (ADP) and thromboxane A2 (TXA2). Here, we aimed to analyze the tyrosine phosphoproteome of platelets activated with the CLEC-2 agonist rhodocytin to identify relevant phosphorylated tyrosine residues (p-Tyr) and proteins involved in platelet activation downstream of this receptor. We identified 363 differentially p-Tyr residues, corresponding to the majority of proteins previously known to participate in CLEC-2 signaling and also novel ones, including adaptors (e.g., DAPP1, Dok1/3, CASS4, Nck1/2), kinases/phosphatases (e.g., FAK1, FES, FGR, JAK2, SHIP2), and membrane proteins (e.g., G6F, JAM-A, PECAM-1, TLT-1). To elucidate the contribution of ADP and TXA2 at different points of the CLEC-2 signaling cascade, we evaluated p-Tyr levels of residues identified in the analysis and known to be essential for the catalytic activity of kinases Syk(p-Tyr525+526) and Src(p-Tyr419), and for PLCγ2 activity (p-Tyr759). We demonstrated that Syk phosphorylation at Tyr525+526 also happens in the presence of ADP and TXA2 inhibitors, which is not the case for Src-pTyr419 and PLCγ2-pTyr759. Kinetics studies for the three phosphoproteins show some differences in the phosphorylation profile. Ca2+ mobilization assays confirmed the relevance of ADP and TXA2 for full CLEC-2-mediated platelet activation. The present study provides significant insights into the intracellular events that take place following CLEC-2 activation in platelets, contributing to elucidate in detail the CLEC-2 signalosome.
Keywords: platelets; CLEC-2 signaling; tyrosine phosphoproteome